Previous resins: a warning to the professional negligence of overtreatment and a new restorative approach to smile construction (Research, Society and Development, 2022)
Every day cosmetic dentistry is an area that has been gaining great popularity among people and professionals and there has been this greater appreciation mainly through social media and in order to meet the demand and expectations of patients there is currently a great development in this area. The objective of this study was to analyze the main techniques used in the composite resin veneers procedure, evaluating their indications, limitations and updates, prioritizing the health and oral harmony of patients. This study was based on dental articles published from 2017 to 2022, on composite resin veneers, following a database, National Library of Medicine (PubMed), Google Scholar and Scietific Electronic Library Online (SciELO). The direct technique consists of the total or partial covering of the buccal surface of the teeth, having its indications and limitations, situations that the dental surgeon must pay attention to so that a satisfactory work is carried out and does not lead to recklessness. In addition, this technique allows associations with others in order to obtain a more harmonious result for the patient. According to the aspects observed, society is increasingly concerned with an immediate result and the main criteria for choosing the technique to be performed is to complete the procedure with only 1 session and cost-effectiveness, when compared to other techniques and it is noted that currently many dentists achieve more satisfactory and safer results using a less invasive approach, with only strategic increments seeking to re-anatomize the tooth and achieve a more harmonious and natural smile.